Identification and Isolation of Small CD44‐Negative Mesenchymal Stem/Progenitor Cells From Human Bone Marrow Using Elutriation and Polychromatic Flow Cytometry. (11th July 2013) - Hall, Sean R.R.; Jiang, Yajuan; Leary, Elizabeth; Yavanian, Greg; Eminli, Sarah; O'Neill, David W.; Marasco, Wayne A.
Abstract : This study used polychromatic flow cytometry and counterflow centrifugal elutriation to identify a phenotypically distinct population of mesenchymal stem/progenitor cells (MSPCs) within human bone marrow (BM). These BM‐MSPCs are rare, small CD45 − CD73 + CD90 + CD105 + cells that lack expression of CD44 and elute early with other adult stem cells; contrary to the widely held view that MSCs are large cells, these MSPCs are absent in later elutriation fractions that contain larger cells such as monocytes. In addition, these MSPCs give rise to mesenchymal stem/stromal cells (MSCs) that have phenotypic and functional properties that are distinct from those of BM‐MSCs purified by plastic adherence. Abstract : The method of isolation of bone marrow (BM) mesenchymal stem/stromal cells (MSCs) is a limiting factor in their study and therapeutic use. MSCs are typically expanded from BM cells selected on the basis of their adherence to plastic, which results in a heterogeneous population of cells. Prospective identification of the antigenic profile of the MSC population(s) in BM that gives rise to cells with MSC activity in vitro would allow the preparation of very pure populations of MSCs for research or clinical use. To address this issue, we used polychromatic flow cytometry and counterflow centrifugal elutriation to identify a phenotypically distinct population of mesenchymal stem/progenitor cells (MSPCs) within human BM. The MSPC activity resided within a population of rare, small CD45 − CD73 + CD90 + CD105 + cells that lack CD44, an antigen that is highly expressed on culture‐expanded MSCs. In culture, these MSPCs adhere to plastic, rapidly proliferate, and acquire CD44 expression. They form colony forming units‐fibroblast and are able to differentiate into osteoblasts, chondrocytes, and adipocytes under defined in vitro conditions. Their acquired expression of CD44 can be partially downregulated by treatment with recombinant human granulocyte‐colony stimulating factor, a response not found in BM‐MSCs derived from conventional plastic adherence methods. These observations indicate that MSPCs within human BM are rare, small CD45 − CD73 + CD90 + CD105 + cells that lack expression of CD44. These MSPCs give rise to MSCs that have phenotypic and functional properties that are distinct from those of BM‐MSCs purified by plastic adherence.